Avison and the Metaphysicals - St.Pierre, Jeannette (My University, 1982)
This study seeks to prove that Margaret Avison can justifiably be considered a metaphysical poet. An analysis is made of the historical, socio-cultural and political conditions that formed Herbert, Vaughan, and Hopkins. The intention is to show that Avison has been subjected to similar stresses during her lifetime as were the metaphysical poets, and that one finds in her work as in theirs evidence revealing a metaphysical tendency of mind. It is shown that Herbert, Hopkins and Avison all perceive the universe as being Christocentric and that all four poets are particularly concerned with the God-Christ-man relationship.
Keywords: English Language and Literature; English Language and Literature